The Implementation of Supreme Court Regulations Number 1/2016 Concerning The Procedure of In-Court Mediation on Economy Sharia Dispute (A Case Study in Blitar Religious Court) - aibak, kutbuddin (The Pontianak State Institute of Islamic Studies, 2019)
The sharia economic dispute resolution process in Indonesia has two paths which can be taken by litigants, namely litigation in court and non-litigation. This research was motivated by sharia economic dispute cases handled by Blitar Religious Court which were carried out through a mediation but failed. The failure of this mediation process and the factors behind the failure are important issues to be studied. Consequently, Supreme Court Regulation No. 1/2016 becomes important to be used as the basis of analysis, whether this regulation has been implemented or not. Therefore, this study aims to describe and analyze the implementation of the Supreme Court Regulation Number 1/2016 concerning the procedure of in-court mediation on economy sharia disputes in Blitar Religious Court, along with various obstacles and solutions.